Implementasi Wakaf Produktif di Indonesia Pasca Berlakunya UU No. 41 Tahun 2004 tentang Wakaf - Nawawi Nawawi (AL-TAHRIR, 2013)
Abstract: Before enacting the law No. 41, 2004 about Islamic pious endowment (waqf), endowment in Indonesia was only meant for immovable properties. This endowment, then, tended to emphasize more on the aspect of preservation of endowment objects rather than the productivity aspects. What was called the productive endowments at that time, then, became a analytical discourse but had not gained the legal endorcment yet. This paper describes the implementation of productive endowment in Indonesia after post enactment the Law No. 41 of 2004 on Waqf. Productive endowment in Indonesia has grown up into two models: endowment in the form of money through Islamic banks and in the form of grant money used as the venture capital of productive endowment development programs from Ministry of Religious Affairs aimed at developing endowment in various sectors of the real economy throughout Indonesia. However, two models of the productive endowment have not gotten enthusiastically reception from the public at least due to two factors. First, the public perception of waqf are understood as mere worship which has nothing to do with the matter of economic development. Second, professionalism in managing Nazhir waqf is so low that make many endowments in Indonesia unproductiveconomically.